2022
DOI: 10.17219/acem/153599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ferroptosis in myocardial ischemia/reperfusion model of rat and its association with Sestrin 1

Abstract: Effects of ferroptosis in myocardial ischemia/reperfusion model of rat and its association with Sestrin 1 [published online as ahead of print on November 22, 2022].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Ferroptosis is a type of iron-dependent programmed cell death, characterized by accumulation of lipid peroxidation products and ROS. 65 LncRNA Mir9-3hg was found to be highly expressed in the exosomes derived from mouse BMSCs and downregulated in H/R-treated cells. 60 Exosomes from BMSCs promoted CMs proliferation, decreased iron ion concentration and ROS level, increased GSH content, and increased Gpx4 (ferroptosis marker protein) levels and decreased ACSL4 levels in H/ R-treated HL-1 mouse CMs, while were reversed by Mir9-3hg siRNA.…”
Section: Exosomal Mir9-3hgmentioning
confidence: 97%
See 3 more Smart Citations
“…Ferroptosis is a type of iron-dependent programmed cell death, characterized by accumulation of lipid peroxidation products and ROS. 65 LncRNA Mir9-3hg was found to be highly expressed in the exosomes derived from mouse BMSCs and downregulated in H/R-treated cells. 60 Exosomes from BMSCs promoted CMs proliferation, decreased iron ion concentration and ROS level, increased GSH content, and increased Gpx4 (ferroptosis marker protein) levels and decreased ACSL4 levels in H/ R-treated HL-1 mouse CMs, while were reversed by Mir9-3hg siRNA.…”
Section: Exosomal Mir9-3hgmentioning
confidence: 97%
“…Increasing studies suggested that MSCs‐derived exosomes might serve as safer alternative approach to cell therapy of MSCs transplantation in MI, which decreased infarcted size and improved cardiac function 64 . Several studies in vitro and in vivo demonstrated that exosomal lncRNAs derived from MSCs exerted important roles on CMs 53–62,65 …”
Section: Cms As Recipient Cells Of Exosomal Lncrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Sestrin2 levels were found to be elevated in ischemic cardiomyocytes [36] and in cardiac macrophages during reperfusion-induced myocardial infarction [37]. However, myocardial ischemia/reperfusion injury was also reported to downregulate Sestrin1 expression in cardiomyocytes [38]. In response to pressure overload, Sestrin2 expression was significantly increased in mouse hearts during early phases, but this reverted back to normal levels at 8 weeks [39].…”
Section: Regulation Of Sestrin Expression In the Heartmentioning
confidence: 99%